Resilience and Environmental Performance of SMEs: The Mediating Role of Ambidextrous Green Innovation - Omar Falah Hasan Al-Obaidy; Ibrahim S. Abdullah Alshammary; Muhammad Ibrahim J. Al-Dulaimi (Journal of Advanced Transportation)
The disruptions in supply chains have put small- and medium-sized enterprises (SMEs) in dire need of resilient supply chains through which they can improve their performance. Based on the resource dependence theory, this study proposes a mediation model to improve the environmental performance (EP) of SMEs. The purpose of this study is to investigate the effect of supply chain resilience (SCR) on EP mediated by ambidextrous green innovation (AMGI). We proved a structural equation model based on questionnaire data from 261 companies in Iraq to test our hypotheses. The results show that SCR has a positive effect on AMGI for proactive and exploitative green innovation dimensions and positive impact on SMEs’ EP. AMGI plays a mediating role and positively affects EP in dimensions. Building SCR requires management support through proactive and reactive measures to address disruption risks. AMGI necessitates integration with supply chain members, including external suppliers and customers, and involves them in developing a corporate strategy that supports environmental issues. By emphasizing EP improvement, this study will guide practitioners in developing innovative techniques that contribute to improving the EP of SMEs and urging decision-makers to support SMEs that include EP within their strategy.